Evaluation of flash glucose monitoring after long-term use: A pediatric survey. Issue 1 (February 2019) - Vergier, Julia; Samper, Martine; Dalla-Vale, Fabienne; Ventura, Valérie; Baucher, Franciane; Joubert, Florence; Pons, Charlotte; De Oliveira, Murielle; Salet, Randa; Faure-Galon, Noémie; Adiceam, Paola; Baechler-Sadoul, Elysabeth; et al.
Highlights: Long-term FreeStyle Libre ® sensor use was studied in a 347 strong pediatric cohort. Patients/parents mainly chose flash glucose monitoring for reasons of comfort. Roughly two in three patients faced difficulties with the device. About two in three were satisfied overall. One third of patients improved their glycemic control. Abstract: Aims: To understand the opinions of children with type 1 diabetes about their everyday use of flash glucose monitoring. (FGM). Methods: Children with type 1 diabetes using the FreeStyle Libre® FGM system and/or their parents were surveyed in several French medical centers between December 2016 and June 2017, regardless of their treatment regimen and metabolic control. Results: Of the 347 patients recruited, 79.5% had been using the sensor for more than three months (average usage time: 285 days). The main reported motivations for initiating this type of monitoring were to avoid finger prick pain (for 85.9% of patients) and to allow parents to check nocturnal glucose levels (60.8%). Two-thirds of respondents experienced difficulties, mainly the sensor falling off (47.6%), measurement discrepancies (25.1%) and cutaneous reactions (22.2%); 89.5% changed their habits: 70.6% took more scans, 37.2% corrected their hyperglycemia more promptly, and 37.5% used trends to adjust their insulin dosage. About one-third of the study group (35.1%) experienced lower HbA1c levels, and two thirds (67.1%) were satisfied with the device. Conclusions: Our results show that FGM is a widely accepted option for self-monitoring diabetes, but that specific training is required to improve its use for insulin dosage adjustment and metabolic results.